2021
DOI: 10.1101/2021.01.05.21249240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fever, Diarrhea, and Severe Disease Correlate with High Persistent Antibody Levels against SARS-CoV-2

Abstract: Lasting immunity will be critical for overcoming the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, factors that drive the development of high titers of anti-SARS-CoV-2 antibodies and how long those antibodies persist remain unclear. Our objective was to comprehensively evaluate anti-SARS-CoV-2 antibodies in a clinically diverse COVID-19 convalescent cohort at defined time points to determine if anti-SARS-CoV-2 antibodies persist an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Many studies have reported that titers of neutralizing antibodies are associated with disease severity [39][40][41] [42]. Our results on multiple linear regression indicated that a collective significant effect exists between the symptoms and antibody levels.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have reported that titers of neutralizing antibodies are associated with disease severity [39][40][41] [42]. Our results on multiple linear regression indicated that a collective significant effect exists between the symptoms and antibody levels.…”
Section: Discussionsupporting
confidence: 54%
“…A single study found no relation between nAb and symptom duration (1‐7 vs 8‐14 vs 15‐28 days) 18 . Similarly, a single study found no correlation between nAb and higher Charlson Comorbidity Index score 14 …”
Section: Resultsmentioning
confidence: 96%
“…Single studies reported a low lymphocyte count 15 or AB/B blood groups as additional proxies: 16 These parameters, albeit not strictly clinical, are widely available for patients discharged from hospitals. One study found that GI symptoms did not predict nAb titer, 17 while another showed that abdominal pain, diarrhea, and low appetite correlated consistently with higher nAb levels 14 . A single study found no relation between nAb and symptom duration (1‐7 vs 8‐14 vs 15‐28 days) 18 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations